Distance sampling survey and abundance estimation of the critically endangered Grenada Dove (Leptotila wellsi). (21st January 2015) - Rivera-Milán, Frank F.; Bertuol, Paulo; Simal, Fernando; Rusk, Bonnie L.
Abstract: The Grenada Dove ( Leptotila wellsi ) is critically endangered; its abundance, as estimated by territory mapping, ranges from 68 to 91 calling males (or 136–182 individuals, assuming a census of paired males). However, an accurate census is unlikely in dry and moist forests, unpaired males may be more detectable than paired males, and sex ratio may be male biased. Because methodology can limit the value of monitoring, we used a systematic grid of survey points and distance sampling to estimate abundance (density and population size), accounting for covariates that may influence detection. Time of day was the most important covariate (e.g., individuals were detected at larger distances early than late in the morning). Density was negatively influenced by disturbance level (deforestation) and positively influenced by food abundance and vegetation cover (leguminous trees). None of the covariates caused extreme heterogeneity; and conventional and multiple-covariate analyses generated similar detection and density estimates, which suggests that model selection was of secondary importance for abundance inferences. Detection probability (mean ± SE) was 0.166 ± 0.031 (95% confidence interval [CI]: 0.114–0.242) within 340 m, density was 0.021 ± 0.004 individuals ha −1 (95% CI: 0.014–0.030), and population size was 160 ± 30 individuals (95% CI: 107–229) in 7, 621 ha. Although spatial distribution was slightly clumped (dispersion parameter: b̂ ∼1.31), we recommend surveying 150 points twice between late July and early August for abundance coefficient of variation (CV) ≤0.15, even if spatial distribution becomes more clumped (e.g., b = 2.5). More survey data are needed to better understand spatial and temporal density variation, test hypotheses about survey design (e.g., road bias in density estimation) and Grenada Dove ecology (rainfall, food, cover, and density correlations), and evaluate management actions (predator removal in nesting areas). With <250 Grenada Doves in the survey region, our data highlight the precarious conservation status of this island endemic, and the urgent need for effective management and targeted monitoring.